Business Result. Advanced Teacher`s Book - Appleby R. Rachel (New York, Oxford University Press, 2010)
Teacher's Боок includes: Teaching notes, ideas, and extra activities, Background information on all unit topics, Progress tests for every unit, DVD worksheets. Teacher training DVD Shows how Business Result works in the classroom. Provides tips on teaching business English. Includes teacher, student, and author commentary. Extra teacher support online. For teacher training notes, photocopiable resources, testing material, wordlists, and course management support, go to www.oup.com/elt/teacher/resultCase studies with the Expert View Every Business Result case study is validated by expert input from Cranfield School of Management. The Expert View provides real-world business authenticity and introduces an authoritative business perspective for your lessons.